PROTEIN AND AMINO ACID METABOLISM AND THEIR ASSOCIATION WITH DISEASES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the biochemical significance of proteins and amino acids in the human body, their metabolic processes, and the diseases that arise as a result of disruptions in these processes. Particular attention is given to hereditary enzyme deficiencies in amino acid metabolism, hepatic (liver-related) disorders, and metabolic syndromes.